2006
DOI: 10.1111/j.1600-051x.2006.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal healing after non‐surgical therapy with a new ultrasonic device: a randomized controlled clinical trial

Abstract: Both the Vector system and S/RP provided favourable periodontal healing results, although in deep pockets S/RP appeared to achieve a better resolution of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 81 publications
5
40
0
1
Order By: Relevance
“…Comparisons between hand instruments and sonic and ultrasonic scalers did not show a clear advantage for the machine driven instruments [3], and traumatisation immediately after instrumentation was similar [4]. Moreover, the use of hand instruments (i.e., conventional Gracey curettes) yielded even greater improvements in some parameters (e.g., bleeding on probing) compared to instrumentation with an ultrasonic system [5]. Other studies have shown that the use of conventional Gracey curettes may result in higher substance loss but significantly better calculus removal [6][7][8] and smoother surfaces compared to sonic and ultrasonic instrumentation [6,9,10].…”
Section: Introductionmentioning
confidence: 95%
“…Comparisons between hand instruments and sonic and ultrasonic scalers did not show a clear advantage for the machine driven instruments [3], and traumatisation immediately after instrumentation was similar [4]. Moreover, the use of hand instruments (i.e., conventional Gracey curettes) yielded even greater improvements in some parameters (e.g., bleeding on probing) compared to instrumentation with an ultrasonic system [5]. Other studies have shown that the use of conventional Gracey curettes may result in higher substance loss but significantly better calculus removal [6][7][8] and smoother surfaces compared to sonic and ultrasonic instrumentation [6,9,10].…”
Section: Introductionmentioning
confidence: 95%
“…The efficiency of VUS for the removal of microbial biofilms has been demonstrated to be as good as conventional periodontal treatment in a study performed by some investigators. 22 The elimination of predisposing factors, including calculus, dental stains, false restorations, and similar factors for the retention of dental plaque in both the VUS and S/RP groups showed to facilitate the effective brushing of the patients. The findings of our study related to dental plaque scores were in accordance with various other studies in which different methods were applied for the nonsurgical periodontal treatment.…”
Section: Discussionmentioning
confidence: 92%
“…These results comply with those of several other studies. 22,24 It was observed that there was a statistically significant reduction in the mean values of PD from the baseline to the 6 th month in the S/RP and VUS groups. In the comparison of the groups, the mean values of PD in the S/RP group declined from 3.74 ±0.55 mm to 2.27 ±0.23 mm.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations